Elbasvir/grazoprevir does not worsen renal function in patients with hepatitis C virus infection and pre‐existing renal disease. Issue 12 (12th May 2017) - Reddy, K. Rajender; Roth, David; Bruchfeld, Annette; Hwang, Peggy; Haber, Barbara; Robertson, Michael N.; Barr, Eliav; Greaves, Wayne
Abstract : Aim: Treatment options have been limited for patients with hepatitis C virus (HCV) infection and chronic kidney disease stage 4/5 (CKD 4/5). The aim of this analysis was to evaluate the impact of elbasvir/grazoprevir (EBR/GZR) on estimated glomerular filtration rate (eGFR) in patients with CKD stage 3 enrolled in phase II/III clinical trials. Methods: We undertook a retrospective integrated analysis of patients with CKD 3 enrolled in the EBR/GZR phase II/III clinical trials. All patients were required to have chronic HCV infection and have received EBR 50 mg/GZR 100 mg, with or without ribavirin, for 8–18 weeks. Patients with CKD 3 (eGFR <60 to ≥30 mL/min/1.73 m 2 ) at baseline plus ≥1 eGFR assessment postbaseline were included. In all studies, the primary endpoint was sustained virologic response 12 weeks after completion of therapy. Results: Thirty‐two patients with CKD 3 were identified from a pooled dataset of 1689 patients enrolled in the EBR/GZR clinical trial program. Thirty‐one (97%) patients achieved SVR12 and one patient relapsed. In these 32 patients, there was no decline in median eGFR at the end of treatment or at follow‐up week 12 compared with baseline. Median eGFR values were 56 mL/min/1.73 m 2 (range, 45–59) at baseline, 58 mL/min/1.73 m 2 (range, 41–78) at the end of treatment and 59 mL/min/1.73 m 2 (range, 38–78) 12 weeks after completing treatment. Discussion: Elbasvir/grazoprevir is a safe and effective treatment option for patients with compromised renal function, irrespective of baseline eGFR.